Loyalty and Disavowal in Holy Qur’an Descriptive linguistic study - Iman Kanani; Zulkifli Mohd. Yusoff (UIN Sunan Gunung Djati Bandung, 2015)
This research aims to clarify the meaning of loyalty and disavowal from linguistic point of view, between the views of linguists, and the exegetes in the Lexicons and exegeses with analysis and debate. First of all, the researcher Indicates definition of loyalty as stated in the dictionaries, with bringing the examples from the Holy Qur’an and the views of the commentators about this issue, then analysis and discussion. Second, he defines Disavowal in the language, with a point of view from linguists, and interpreters, by analyzing and discussion the examples from the Noble Qur’an. Finally, it illustrates the application of the legal and practical concept of loyalty and disavowal, to enhance the significance of language. The importance of the current study is- according to researcher’s information- due to its doctrinal and sociological matter and nobody precede such a linguistic study of Loyalty. This research approaches the issue, using the method of descriptive and analytical, based on the description and analysis of the phenomenon.